Implementasi Etika Bisnis Islam Dalam Transaksi Jual Beli Online Pada E-Commerce Popular Di Indonesia - Qanitah An Nabila A'yun; Nafisah Maulidia Chusma; Cindy Nurul Aulia Putri; Fitri Nur Latifah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This research aims to analyze and know the implementation of Islamic business ethics on online buying and selling transactions on the most popular e-commerce in Indonesia. This research method is qualitative that uses the field of literature review. Data collection is done by collecting the source of articles in the form of journals and previous proceedings as many as 13 selected articles that are relevant. The results of this study can be concluded that online buying and selling transactions on e-commerce Shopee, Tokopedia, Lazada, and Bukalapak in their application have tried to conform to Islamic business ethics, but some cases of human error or lack of understanding of sharia economy are good and correct from the agency and users, this causes doubts about the implementation of Islamic sharia principles in e-commerce.